Learning about Extraordinary Beings: Native Stories and Real Birds - Raymond Pierotti (Ethnobiology Letters, 2020)
Oral traditions of Indigenous American peoples (as well as those of other Indigenous peoples) have long been discussed with regard to their reliability as metaphorical accounts based upon historical knowledge. I explore this debate using stories to discuss the importance of the role of Corvidae in Indigenous knowledge traditions and how these stories convey information about important socioecological relationships. Contemporary science reveals that Corvids important in cultural traditions were companions to humans and important components of the ecology of the places where these peoples lived. Ravens, Crows, Jays, and Magpies are identified as having special roles as cooperators, agents of change, trickster figures, and important teachers. Canada (or Gray) Jays serve as trickster/Creator of the Woodland Cree people, Wisakyjak. Magpies won the Great Race around the Black Hills to determine whether humans would eat bison or vice versa. I analyze these stories in terms of their ecological meaning, in an effort to illustrate how the stories employ dramatic settings to encourage respect and fix relationships in the sociocultural memory of the people.